The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1002/(sici)1097-010x(19981015)282:3<332::aid-jez6>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Putative multiadhesive protein from the marine sponge Geodia cydonium: Cloning of the cDNA encoding a fibronectin‐, an SRCR‐, and a complement control protein module

Abstract: Sponges (Porifera) representing the simplest metazoan phylum so far have been thought to possess no basal lamina tissue structures. One major extracellular matrix protein that is also a constitutive glycoprotein of the basal lamina is fibronectin. It was the aim of the present study to identify the native protein from the marine sponge Geodia cydonium and to isolate the corresponding cDNA. In crude extracts from this sponge protein(s) of M(r) of approximately 230 and approximately 210 kDa could be visualized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…10 In line with these studies it could be clarified, mainly from results with the marine sponges Suberites domuncula and Geodia cydonium, that Porifera have molecules similar to those known from the mammalian innate immune system, such as molecules containing scavenger receptor cysteine-rich domains, 11,12 cytokine-like molecules 13 or members of the (2'-5')oligoadenylate pathway. 14 ± 16 Furthermore, it could also be shown that`precursors' of the second type of immune response in mammals, the adaptive immune system, are present in sponges.…”
Section: Introductionmentioning
confidence: 93%
“…10 In line with these studies it could be clarified, mainly from results with the marine sponges Suberites domuncula and Geodia cydonium, that Porifera have molecules similar to those known from the mammalian innate immune system, such as molecules containing scavenger receptor cysteine-rich domains, 11,12 cytokine-like molecules 13 or members of the (2'-5')oligoadenylate pathway. 14 ± 16 Furthermore, it could also be shown that`precursors' of the second type of immune response in mammals, the adaptive immune system, are present in sponges.…”
Section: Introductionmentioning
confidence: 93%
“…Sponges constitute the oldest and lowest metazoan phylum; within them, Geodia cydonium, from the family Geodiidae, represents the oldest living group (Mü ller et al, 1999). Several alternatively spliced forms of an SRCR group A protein and a group B protein have been identified in G. cydonium (Pancer et al, 1997;Pahler et al, 1998). The group A protein has both membrane-bound and soluble forms, whereas the SRCR domain of MAP_GEOCY, the group B protein, displays high homology with those of CD5 and CD6.…”
Section: Phylogeny and Ontogenymentioning
confidence: 99%
“…The molecules identified, cloned, and expressed from sponges, mainly from Geodia cydonium and Suberites domuncula, are cell membrane receptors that are not found in fungi, plants, or Protozoa, e.g., the receptor tyrosine kinase (Müller and Schäcke 1996;Wimmer et al 1999a), integrin (Pancer et al 1997a;Wimmer et al 1999b), receptors comprising scavenger receptor cysteine-rich repeats (Pancer et al 1997b;Blumbach et al 1998), a putative multiadhesive basal lamina protein (Pahler et al 1998b), a neuronal-like metabotropic glutamate-like receptor (Perovic et al 1999), and the sponge adhesion molecules with two immunoglobulin-like domains in the extracellular part that display sequence similarity to the human inhibitory receptor Kir or to the T-cell receptor (Blumbach et al 1999;Müller et al 1999b). Furthermore, immune molecules, cytokine-like as well as immune modulatory molecules, identified in sponges, have also not yet been found in nonmetazoan organisms.…”
Section: Introductionmentioning
confidence: 99%